Indigenous food production system and the impact of population growth: community-based examples with anthropological evidence - Karim, A.H.M Zehadul (Canadian Center of Science and Education, 2014)
It is reported that 99% of human food on this planet Earth usually comes from terrestrial environment, and the remaining 1% is extracted from other aquatic sources (see FAO, 2002). Thus, it is indicative that land is essentially the most fundamental resource-base for food production and people have long been utilizing their land by adopting their own indigenous knowledge to boost food production from agrarian sources. An excessive population growth has a consequential effect on agricultural resource-base, where a huge amount of farming land has drastically been reduced in the past few decades; and that process is still continuing. Meanwhile, it is reported that only 12% of the total land allowed the production of food and cereals which does not seem to be sufficient to cover the subsistence of a huge number of people around the world (see Buringh, 1989). Contextually, I formulate a clear statement saying that due to an excessive demographic pressure, the farmers around the world go for a mechanized cultivation by making a transformation of their indigenous traditional food production system to a more intensive mechanized cultivation. The resulting effect is the degradation of the soil which keeps land fully dependent on organic manure and mechanized irrigation, putting the environment in a vulnerable situation. To understand this, the paper has cited a few examples from different regions of the world, and simultaneously, has described facts from one specific ethnographic case study from a South Asian community. Based on the above ideas, I conclude it with a modest caution saying that we must find some preventive mechanisms to keep our population at a replacement level. This will eventually allow us to revert back to our indigenous food production system, which seems to be essential to make our planet earth more natural and habitable for the future generation.